2021
DOI: 10.52289/hej8.101
|View full text |Cite
|
Sign up to set email alerts
|

The sidewalk is a history book: Reflections on linking historical consciousness to uses of history

Abstract: The ongoing discussion about what constitutes historical consciousness is intensifying within the growing international community of history-education researchers. What started as an exploration of how life outside schools affects our historical thinking has become a key concept for structuring formal education. This shift has largely been positive; however, there are reasons for caution. If practical adaption means outlining, classifying, and measuring levels of achieved awareness, it also presents a risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Likewise, in Sweden, Börnfors (2001) noted that family historians often connected their motivations to tangible (e.g., photographs) and intangible (e.g., stories) inheritances that led to a sense of belonging and cultural embeddedness (identity). This reflects the portrayal of family history as a move of interest from the traditional disciplinary focus of notable events and famous individuals (e.g., wars and royalty) towards the banal, unremarkable or commonplace, embedded symbols and objects of historical narratives (Billig, 1995;Edquist, 2009;Karlsson, 2011;Nordgren, 2021;Shaw, 2021). Similarly, researchers found that motivation and reasoning can be related to one's lifespan and a desire to produce a legacy for future generations (Evans, 2023;Moore & Rosenthal, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Likewise, in Sweden, Börnfors (2001) noted that family historians often connected their motivations to tangible (e.g., photographs) and intangible (e.g., stories) inheritances that led to a sense of belonging and cultural embeddedness (identity). This reflects the portrayal of family history as a move of interest from the traditional disciplinary focus of notable events and famous individuals (e.g., wars and royalty) towards the banal, unremarkable or commonplace, embedded symbols and objects of historical narratives (Billig, 1995;Edquist, 2009;Karlsson, 2011;Nordgren, 2021;Shaw, 2021). Similarly, researchers found that motivation and reasoning can be related to one's lifespan and a desire to produce a legacy for future generations (Evans, 2023;Moore & Rosenthal, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…The participants were open to a newly constructed future or value-laden life orientation by "making use of history" (Nordgren, 2016(Nordgren, , 2021, the people in their history, and their identity. The participants seemed to have constructed their own stories as a way to critically orient their own lives and even use history to ask themselves existential questions equated with history.…”
Section: Developing Narrative Competencementioning
confidence: 99%
“…They connect to society's politics of memory, to the transformation of historiography, to changes to the perception of knowledge and to the rapid rise of digitalization. In recent years, the view has become generally accepted in international circles of discourse that the conventional model of history teaching does not sufficiently equip students with the knowledge to face the diversity and complexity of today's democratic society or the great global challenges of our age (Haydn, 2019;Nordgren, 2021).…”
Section: Introduction © 2023 the Author(s) The International Context ...mentioning
confidence: 99%